2017 External Sector Report Individual Economy Assessments. (Policy Papers; Policy Paper ;, 2017)
The external sector assessments use a wide range of methods, including the External Balance Assessment (EBA) developed by the IMF's Research Department to estimate desired current account balances and real exchange rates (see IMF Working Paper WP/13/272 for a complete description of the EBA methodology and Annex I of the 2015 External Sector Report for a discussion of more recent refinements). In all cases, the overall assessment is based on the judgment of IMF staff drawing on the inputs provided by these model estimates and other analysis. Since estimates are subject to uncertainty, overall assessments are presented in ranges. The external sector assessments are based on data and IMF staff projections as of June 15th, 2017. The external assessments discuss a broad range of external indicators: the current account, the real effective exchange rate, capital and financial accounts flows and measures, FX intervention and reserves and the foreign asset or liability position.[1] The individual economy assessments are discussed with the respective authorities as a part of bilateral surveillance.